(untitled) (Al-Academy, 2022)
Maher Harbi’s drawings have taken an aesthetic and artistic dimension that leads to creating an approach between what is religious and mundane, between religious and mundane, with the techniques of plastic art, and this is what led the researcher to address this topic and stand on the realistic controversy based on the religious and the secular. Accordingly, the researcher divided the subject of the research into four chapters. The first chapter (the methodological framework) dealt with the research problem, which is summarized in the following question: (What is the dialectic of the reality of Maher Harbi’s drawings between the religious and the secular?) Then the importance of the research manifested in shedding light on the deep structure of the drawings and its dimensions in the religious reality and mundane. As for the need to research an academic study that benefits students in the fine arts specialization.The chapter also dealt with the objective of the research, which seeks to: (know the dialectic of religious and worldly reality in Maher Harbi’s drawings). This is followed by the limits of the research that include the temporal limit: (1990-2014) and the spatial limit: (Nineveh Governorate) and the subject boundary (a dialectical study of the religious and worldly reality in Maher Harbi’s drawings) to conclude the research by defining the terms (argumentative, religious, worldly) linguistically, idiomatically and procedurally.As for the second chapter (the theoretical framework), it included two topics: the first: the Christian religious dimensions of painting, and the second: the religious and secular dialectic in art. The researcher concludes the chapter with the indicators that resulted from the theoretical framework and previous studies.The third chapter includes (the research community), which is defined in Nineveh Governorate (the research tool), as the researcher adopted the indicators that resulted from the theoretical framework as the criterion for measuring the research sample. (Selected models between 1995, 2011), to end the chapter with the analysis of samples.The fourth chapter also dealt with the research results and their discussion, then the conclusions, recommendations and suggestions. This is followed by a list of proven sources, references, appendices and images.